Media Convergence in Fajar Daily Newspaper - Rahmita Saleh*; Muhammad Yusuf; Mariesa Giswandhani (Universitas Syiah Kuala, 2023)
This research was conducted to determine the media convergence applied by the Fajar Daily newspaper based on the Siepera and Veglis models. This model consists of four forms, namely technology convergence or multiplatform, business convergence, professional convergence and content or multimedia convergence. Each form is described based on the practices carried out by the Harian Fajar newspaper through qualitative methods. The results of the study show that Fajar Daily applies these four models wherein the convergence of innovation technology is carried out by combining three platforms to present news and information to readers, namely print media, online media and social media. This convergence stage is in line with content convergence where adjustments to news content have been made on each platform but there are weaknesses in the support/promotion of content between platforms which is still carried out only in print and online media. In terms of business and professional convergence, Fajar Daily's management has endeavored to develop the business in a multi-platform direction.